2022
DOI: 10.3390/su142113998
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Stacking Ensemble Learning Model for Breast Cancer Detection and Classification Using Machine Learning

Abstract: Breast cancer is the most frequently encountered medical hazard for women in their forties, affecting one in every eight women. It is the greatest cause of death worldwide, and early detection and diagnosis of the disease are extremely challenging. Breast cancer currently exceeds all other female cancers, including ovarian cancer. Researchers can use access to healthcare records to find previously unknown healthcare trends. According to the National Cancer Institute (NCI), breast cancer mortality rates can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Several other methods were also introduced to classify breast cancer [ 34 ]. Few other studies also existed in the literature that proposed deep learning-based frameworks for breast cancer classification, such as the optimized stacking learning approach [ 35 ], fuzzy c-mean and median support value-based CNN approach [ 36 ], and named a few more [ 37 ].…”
Section: Related Workmentioning
confidence: 99%
“…Several other methods were also introduced to classify breast cancer [ 34 ]. Few other studies also existed in the literature that proposed deep learning-based frameworks for breast cancer classification, such as the optimized stacking learning approach [ 35 ], fuzzy c-mean and median support value-based CNN approach [ 36 ], and named a few more [ 37 ].…”
Section: Related Workmentioning
confidence: 99%
“…Under these four study conditions, hot-wet Test specimens deployed in the atmosphere, increased compared to untreated samples Deboning and exhibiting matrix cracking. CFRP composites are absorbed by the matrix the amount of moisture increases cracking and tensile strength it clearly states that reduces [20].…”
Section: Cfrp Compositesmentioning
confidence: 99%
“…Their results indicated that the Logistic Regression model achieved 98% accuracy, surpassing the performance of random forest, decision tree, and K-NN algorithms. Kumar et al 12 developed an optimized stacked integrated learning (OSEL) model for early breast cancer prediction utilizing a dataset from the University of California Irvine repository. Their approach demonstrated higher accuracy compared to individual machine learning prediction models such as AdaBoostM1, Gradient Boosting, Stochastic Gradient Boosting, CatBoost, and XGBoost.…”
Section: Introductionmentioning
confidence: 99%